Protective effect of dexmedetomidine combined with remifentanil on perioperative brain tissue in patients with severe traumatic brain injury and its influence on serum inflammatory markers - Luo Taotao; Zhang Xuezhi; Luo Yating; He Boqi; Xie Yongle (Vojnosanitetski Pregled)
Background/Aim. Patients with a severe traumatic brain injury (TBI) demand intensive monitoring and treatment due to significant brain trauma or other accompanying causes, such as comorbidities or polytrauma. Patients with such injuries are under intense stress, leading to increased sympathetic excitability, and often experience agitation and pain. Appropriate sedation and analgesia are crucial for these patients, as they can reduce complications, mortality, and sequelae and improve quality of life. The aim of this study was to examine the impact of dexmedetomidine combined with remifentanil on postoperative sedation, analgesia, and cerebral oxy-gen metabolism in patients with TBI. Methods. A prospective, single-blind, randomized, controlled clinical study included 80 patients divided into two groups: a control group (CG) that received dexmedetomidine (n = 40) and an observation group (OG) that received dexmedetomidine combined with remifentanil (n = 40). Results. Compared to CG, OG demonstrated superior sedation and analgesia, reduced sedation and mechanical ventilation durations, and lower heart rate, mean arterial pressure, and respiratory rate. Additionally, OG showed statistically greater reductions in inflammatory markers and serum cortisol levels and higher β-endorphin levels. Cerebral oxygen metabolism indices also improved more in the OG postoperatively, although the differences were not statistically significant. Conclusion. Sedation and pain management strategy using of dexmedetomidine combined with remifentanil improved patient outcomes by speeding recovery and reducing physiological stress. Additional research is needed to determine the long-term effects of this combination on brain oxygen metabolism